Development of an interactive Android application for learning Hijaiyah letters with educational audio and visual features using the Waterfall method - Leni Marlina; Suheri; Aulia Fadhillah (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to develop and test the effectiveness of Android-based hijaiyah letter learning mobile applications as an interactive learning medium for beginners. The background of the research is based on the challenges in learning hijaiyah letters conventionally and the potential for the use of mobile technology to increase learning effectiveness. The research method uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. System design uses an object-oriented approach with Unified Modeling Language (UML) to ensure a structured application architecture. The application development is carried out using Android Studio with the Kotlin programming language and implements the concept of M-Learning (Mobile Learning) by integrating interactive features such as audio pronunciation, letter writing animations, and mini games for learning evaluation. The test involved 150 respondents consisting of children aged 5-12 years and TPQ/TPA teachers. The results of the study showed a significant success rate with an increase in the ability to recognize hijaiyah letters by 85% compared to conventional methods. The user satisfaction level reaches 92%, with the aspects of ease of use and interactivity receiving the highest rating. This application also succeeded in increasing students' interest in learning by up to 78% based on observations and feedback from teachers. In conclusion, the mobile application for learning hijaiyah letters developed has proven to be effective as an alternative learning medium and a complement to conventional methods in recognizing hijaiyah letters.